Analisis Kebijakan Sekolah untuk Mengembangkan Mutu Internal Pendidikan Siswa SMP Istiqlal Deli Tua - Ahmad Mukhlasin; Saniah Nurhasanah; Reihan Kamila Hasri; Muhammad Gembira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Learning is a key element in building a nation's civilization. The level of learning understood by a community will have a significant influence on the lifestyle that will be created. The position of learning in achieving progress in various aspects of life, such as social, political, cultural and economic, cannot be questioned. This research is carried out using qualitative methods, namely research that is carried out through observation and seeking information directly in research positions or in other words it can be said as field research. This research uses a phenomenological approach by explaining and describing phenomena that occur in conditions in the field. In this case, researchers want to explain and describe the impact of School Policy Analysis to Improve the Internal Quality of Learning for Istiqlal Deli Tua Middle School Students. Istiqlal Deli Tua Middle School's policy in formulating its vision and mission shares the main focus on aspects of morality. Determining the direction of the vision and mission is influenced by close social interactions and the various backgrounds of students. The process of formulating policies at Istiqlal Deli Tua Middle School involves various parties, including internal schools, student parents, and other policy makers, in order to improve learning progress. This personal learning option as a school policy is not carried out without a reason, but rather is adjusted to the vision and mission that form the basis. learning system in the school. To realize this policy, the school has designed a management system and implementation guidelines that include regular, automatic activities and exemplary examples inside and outside the classroom. The conclusions of research on the analysis of school policies to improve the internal quality of student learning include an explanation of the important role of school policies in providing direction and support. Management of energy resources, including the allocation of funds and development of teaching staff, and the involvement of all related parties, such as teachers, parents, students and local communities, are considered important in achieving the goal of quality learning. Continuous monitoring and assessment are key aspects for identifying revision zones and adapting school policies. A focus on improving the educational process, innovative teaching methods, and long-term educational support are also recognized as elements that can provide positive impacts. Finally, adapting to changes in learning areas, such as technological growth, curriculum changes, and social dynamics, is considered important and requires flexibility in school policies. However, it is necessary to explain that this conclusion is universal and needs to be confirmed by specific findings from actual research